The Domestic Livestock Resources of Turkey: Populations, Production and Pathology of Ducks and Geese - Wilson , R. Trevor; Yilmaz, Orhan (International Journal of Poultry Science, 2013)
Turkey is home to a broad range of domestic livestock species that includes ruminant and monogastric quadrupeds and at least eight species of poultry. Ducks and geese are minor species of poultry in terms of numbers but are spread over most of the country (with concentrations of geese in the northeast) and are owned mainly by resource-poor smallholder farm families to whom they contribute animal protein and thus improve welfare. Government recognizes only one indigenous breed of each species but there are various colour morphs of both ducks and geese and these show differences in egg weights and growth traits. Some exotic Pekin ducks were imported in 1984 and Muscovy ducks at an unknown time. There were attempts to modify the genome of local geese with imports of Romanola eggs in 1988 and French White eggs in 1992. There has been limited research on disease in the two species. Most production is for home consumption so there is little internal market activity but there have been sporadic exports and exports of duck meat and goose foie gras. Government has a policy statement on duck and goose production but does not support or promote any conservation activities. There are both technical and administrative challenges to improved and increased production of ducks and geese but opportunities exist for enterprise diversification, for new entrants to species that are less costly to keep and produce than many other domestic species and for processing and producing value-added products.